Epistemologías feministas en los sures comunitarios e indígenas. - ALVARADO, MARIANA (Nomadías)
Some feminisms, in and from the south, propose to revise to the epistemic of modern Western thought in an attempt to inhabit an externality detached from the Euronortecentrated logos. In and from the south certain feminisms reflect. These feminisms inhabit the externality of the modern patriarchy western colonial matrix, detached from the Euro-North-centered logos. This writing wants to listen to what community feminisms have to say in the voices of Lorena Cabnal and Aura Cumes.